2011
DOI: 10.1002/elps.201100012
|View full text |Cite
|
Sign up to set email alerts
|

Sequential injection setup for capillary isoelectric focusing combined with MS detection

Abstract: Capillary isoelectric focusing in the presence of electroosmosis with sequential injection of carrier ampholytes and sample was found to be suitable for MS detection. The separate injection of the sample and the ampholytes provides good condition to suppress and overcome the undesirable effect of the presence of ampholytes in MS. By the appropriate selection of ampholyte solutions, whose pH range not necessarily covers the pI values of the analytes, the migration of the components can be controlled, and the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…CIEF online coupled to MS requires volatile electrode solutions, such as formic acid and ammonium hydroxide . In this simulation work and before , H 3 PO 4 and NaOH were used as anolyte and catholyte, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIEF online coupled to MS requires volatile electrode solutions, such as formic acid and ammonium hydroxide . In this simulation work and before , H 3 PO 4 and NaOH were used as anolyte and catholyte, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Further work was focused on natural narrow range pH gradients that did not or barely include neutrality, i.e. to gradients such as those formed in the pH 5–7 and 7–9 intervals employed in experimental studies and the pH 6.7–7.7 gradient used for hemoglobin analysis . In this paper, simulation data of narrow range carrier ampholyte based pH gradients that end or begin at, shortly before or shortly after pH 7.00 are presented for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Páger et al. demonstrated a successful CIEF‐MS hyphenation using this approach by separate injection of the sample and the ampholyte . All general parameters are summarized in Table .…”
Section: Technical Strategies For Cief‐msmentioning
confidence: 99%
“…The major questions are about the use of coated or uncoated capillaries, the composition of catholyte and anolyte, and most importantly about the amphoteric compounds providing the pH gradient, i.e., the use of ampholytes or other substances. For the MS detection, it is highly advisable to use electrolytes, which are compatible with MS, and one should consider the application of ampholytes (or other compounds) at concentrations, where the suppression of the analyte ionization is not present, or it is low . Páger et al.…”
Section: Introductionmentioning
confidence: 99%
“…Páger et al. successfully demonstrated hyphenation of CIEF with MS after sequential injection of amphoteric dyes and the carrier ampholytes, and showed that separation can be reached also with one separate ampholyte zone, too (before or after the sample zone). Computer simulations have been performed to see the effect of various sampling strategies in CIEF , studying the behavior of sample components with pI values outside the pH gradient of the ampholytes .…”
Section: Introductionmentioning
confidence: 99%